The Role of Cognitive Control in Older Adult Cognitive Reappraisal: Detached and Positive Reappraisal - Liang, Ying; Huo, Meng; Kennison, Robert; Zhou, Renlai (Frontiers in Behavioral Neuroscience, 2017)
Older adults are more likely to regulate their emotions by engaging in cognitive reappraisal. However, depending on the type of cognitive reappraisal used, efforts to regulate emotions are sometimes met with success and other times with failure. It has been suggested the well-known age-related decline in cognitive control might be the culprit behind the poor use of detached reappraisal by older adults. However, this possibility has not been thoroughly investigated. In addition, studies have not examined what aspects of cognitive control– shifting, updating or inhibition–might be relevant to cognitive reappraisal. In the present study, 41 older participants were tested on cognitive control and abilities to use detached and positive reappraisal. Results showed detached reappraisal compared to positive relied more heavily on cognitive control, specifically mental set shifting. Results of this study have important implications for development of cognitive training interventions for older adults.